2015
DOI: 10.1007/s12070-015-0956-y
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Profile in Primary Sjögren’s Syndrome in a Tertiary Care Setting and its Clinical Implications

Abstract: This study aims to assess the frequency and the profile of hearing loss among patients with primary Sjögren's syndrome in a tertiary care hospital in India and to look for an association between hearing loss and immunological parameters (anti-SSA antibody, anti-SSB antibody, anticardiolipin antibodies, complements C3 and C4). This prospective observational study was done from January 2011 to October 2011 on consecutive patients diagnosed with primary Sjögren's syndrome in our tertiary care hospital. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…A significant difference at 125-250-500 Hz between the groups was obtained, differently from some other studies [6]. The statistically significant differences between the pSS and control groups were detected not only at very high frequencies but also in all other frequency ranges (low, middle, high), unlike other studies [7]. The auditory damage resulting from pSS was particularly seen at very high frequencies in the current study, which is supported by some other studies about high-frequency audiometry thresholds of pSS [6,8].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…A significant difference at 125-250-500 Hz between the groups was obtained, differently from some other studies [6]. The statistically significant differences between the pSS and control groups were detected not only at very high frequencies but also in all other frequency ranges (low, middle, high), unlike other studies [7]. The auditory damage resulting from pSS was particularly seen at very high frequencies in the current study, which is supported by some other studies about high-frequency audiometry thresholds of pSS [6,8].…”
Section: Discussioncontrasting
confidence: 90%
“…The present study also investigated middle ear pressures, static compliances, and statistical analyses of these values between the groups. Little research has examined tympanometry results comprehensively [7,8]. Only evidence about the type of tympanogram was presented in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, elevation of IL-1β has been demonstrated to be implicated in the activation of the IL-1 signaling pathway, which plays an important role in the pathogenesis of various autoimmune diseases. 5 Airway inflammation and immune factors play an important role in the pathogenesis of asthma. It has been reported that IL-1β induction as well as the activation of IL-1 signaling in sputum are implicated in airway neutrophilia and inflammasome activation during asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, antigen stimulation causes an increase in IL‐1α and IL‐1β, the typical innate immune cytokines involved in the initiation and persistence of inflammation, in peripheral blood mononuclear cells (PBMCs) during the exacerbation of asthma 4 . Furthermore, elevation of IL‐1β has been demonstrated to be implicated in the activation of the IL‐1 signaling pathway, which plays an important role in the pathogenesis of various autoimmune diseases 5 …”
Section: Introductionmentioning
confidence: 99%